Progressive Ureteropelvic Junction Obstruction and Renal Function Deterioration in Adult, Even in a Short Period of Time - Abbas Basiri; Behzad Narouie; Saeed Reza Ghanbarizadeh; Hamidreza Rouientan; Mohadese Ahmadzade (Case Reports in Urology)
Introduction. The ureteropelvic junction obstruction is more common in children; however, it can also affect adults. The management of this condition has shifted toward a nonoperative approach with serial ultrasonography and renography. Case Presentation. The ureteropelvic junction obstruction imaging with significant renal function deterioration in an adult patient is described in this report. Laparoscopic exploration revealed aberrant vessels that compress the ureteropelvic junction against the lower pole of the kidney. Conclusion. It is important to consider that some of the ureteropelvic junction obstruction cases can get worse even in a short period of time.